2012
DOI: 10.1002/prot.24136
|View full text |Cite
|
Sign up to set email alerts
|

Crystal packing modifies ligand binding affinity: The case of aldose reductase

Abstract: The relationship between the structures of protein–ligand complexes existing in the crystal and in solution, essential in the case of fragment-based screening by X-ray crystallography (FBS-X), has been often an object of controversy. To address this question, simultaneous co-crystallization and soaking of two inhibitors with different ratios, Fidarestat (FID; Kd = 6.5 nM) and IDD594 (594; Kd = 61 nM), which bind to h-aldose reductase (AR), have been performed. The subatomic resolution of the crystal structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Studies on larger ligands have at least shown differences in the affinity in solution and solid state. [29] Additionally in crystallography, ligands have to pass through crystal packing channels to reach the binding site on the protein. These channels can block access, in the simplest case due to steric reason, but electrostatics or hydrophobic barriers can also hamper successful diffusion to the binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on larger ligands have at least shown differences in the affinity in solution and solid state. [29] Additionally in crystallography, ligands have to pass through crystal packing channels to reach the binding site on the protein. These channels can block access, in the simplest case due to steric reason, but electrostatics or hydrophobic barriers can also hamper successful diffusion to the binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Especially surface‐exposed parts of the complex may undergo conformational changes due to interactions with adjacent molecules in the crystal . Also the binding mode of a ligand and the affinity of a ligand for a protein can be influenced by the crystal environment . Thus, when geometrical aspects of the binding between a ligand and a protein are analyzed, one should keep in mind that the binding can be an artifact of the crystal packing.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, native MS was used to demonstrate that crystal packing environment alters the relative binding affinity of aldose reductase for two different inhibitors. 54 Native MS has also been successfully used to investigate the effect of inhibitors on a protein:RNA complex. 55 Another study that combined native MS with X-ray crystallography concerned two nickel import proteins of Staphylococcus aureus.…”
Section: Protein-ligand Interactions Studied By Native Q-tof Based Msmentioning
confidence: 99%
“…The authors used native MS to confirm the 2:1 binding stoichiometry for one of these compounds and to rule out a crystal packing artefact. By contrast, native MS was used to demonstrate that crystal packing environment alters the relative binding affinity of aldose reductase for two different inhibitors . Native MS has also been successfully used to investigate the effect of inhibitors on a protein:RNA complex .…”
Section: Introductionmentioning
confidence: 99%